International mobility of young adult Spaniards eight years after the onset of the economic crisis. Food for thought - Josefina Domínguez-Mujica; Juan Parreño-Castellano; Ramón Díaz-Hernández; Claudio Moreno-Medina (Belgeo)
Eight years after the economic crisis began in Spain (2008), its impact on migration trends is due for re-examination. The emigration of young Southern Europeans during the crisis, motivated by high unemployment and the lack of opportunities, has been analysed by various academics. These scholars have highlighted the modification of migration patterns in Portugal, Spain, Italy and Greece, countries with a positive net migration rate during the years of economic growth, and have studied the reversion to their former status as net emigration countries during the recession. However, despite the fact that today, eight years after the onset of the crisis, the economy has begun to show signs of recovery, there is evidence that migration trends among young Spaniards have changed. Consequently, the main hypothesis of this paper is that Spanish migration patterns have been altered by a tendency towards higher mobility at the dawn of the post-crisis era.